ISTIDLAL ISLAMIC LAW OF KURBAN WITH MONEY ACCORDING TO ISLAMIC ECONOMY - Nurhadi . (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Indeed the money distributed with the sacrificial intention becomes charity, because the money is included in the provision of Allah. While the sacrifice is also essentially the charity of money (property) bought by animals, then slaughtered, then given to the neighbors and the most important to the poor. The amount of reward for charity reward is doubled as explained in the paragraph above. Then if the sacrifice as a form of annual worship (10-13 zulhijjah) that was carried out was not accepted as a sacrifice just because of carrying out it in the form of the distribution of money, not sacrificial meat? Istinbath of sacrificial law with money, namely the Qur'an (Surah Al-Hajj: 28 and 36), hadith (HR. Abu Musa), atsar (Ayesha and Bilal), qias (diaciaskan with zakat), istihsan (better ), istishab (al-Ashlu fi syai al-Ibahah), istislah (maslahat), maqashid sharia (the purpose of the Shari'a is the benefit of the afterlife) and legal contextualism (filasfat, the nature and meaning of the Shari'a) and the principle of benefit and benefit (jalbu al -Mashalih wa dar'u al-Mafasid), whereas in muamalah the basic Islamic economy of every thing is permissible unless there is a argument which prohibits it. In the context of sacrifice with money in the perspective of Islamic economics in terms of the law of sacrifice there is no text on the prohibition of sacrifice with money, from an economic standpoint, more money is needed than sacrificial meat, it can be understood that sacrifice with money due to the condition of the situation and the presence of the victim receives more money rather than sacrificial meat, the law may (conditionally) namely al-Ibahah and the sacrifice is valid.